KNOWLEDGE SHARING MANAGEMENT: STRATEGY FOR IMPROVING THE QUALITY OF HUMAN RESOURCES - Hasan Baharun; Hefniy Hefniy; Silviani Silviani; Muhammad Anas Maarif; Adi Wibowo (JURNAL AL-TANZIM, 2021)
This study aims to analyze and understand about analyzing the knowledge sharing strategy carried out by SMA Nurul Jadid, Paiton, Probolinggo in improving the quality of its human resources. This research uses a qualitative approach to the type of case study. Data collection techniques are carried out through interviews, observation, and documentation. Data analysis was carried out through display data, data reduction and conclusion drawing. The results showed that the strategy to improve the quality of human resources through knowledge sharing at SMA Nurul Jadid was carried out through; utilize materials, talk space, knowledge sharing culture, benchmarking best practices.